A justiça em John Rawls, Amartya Sen e Philip Pettit: uma nova abordagem da liberdade - Lucas Soares Rodrigues (2017)
The present work aims to discuss contemporary theories of justice, in search of room for a more effective sense of freedom within the scenario of political philosophy. To do this, this Dissertation is structured as follows: first, it analyzes John Rawls´ theory of justice, and its limitations regarding transcendental institutionalism and the primary goods; second, it puts forward Amartya Sen´s notion of capabilities, which is more effective in dealing with individuals in real societies; and finally, it approaches the republicanism of Philip Pettit and its ideal of freedom as non-domination, which fills in some gaps of Sen´s theory, at the same time that associates his theory with republicanism. Thus, we will try to show how, through a link among the three authors, a more robust theory of justice can be developed with regard to the real freedoms of individuals in contemporary democratic societies